An Angiosarcoma in the Right Atrium: A Case Report - Nicoleta Dumitru; Daniela Bartos (Journal of Biomedical & Clinical Research)
Angiosarcoma is a rare malignant tumor of vascular endothelial cell origin, accounting for 1-2 % of all sarcomas. We present a 24-year-old female patient, initially diagnosed and treated for tuberculous pleurisy for one month. Then transthoracic echocardiography (TTE) revealed a rare cause for the pleural and pericardial effusion - a tumoral mass apparently arising from the right atrium and extending into the upper vena cava. The patient presented with worsening dyspnea, stabbing pain in the right hemithorax and persistent, irritating cough, a recent history of haemoptysis, bilateral pleurisy and hemorrhagic pericardial effusion. The ECG showed sinus rhythm with negative T-waves in leads DI, Dll, aVL, V3 to V6. The TTE showed an irregularly shaped right atrial tumoral mass, not resembling a thrombus, which extended to the upper vena cava. The transesophageal echocardiography showed an invasion of the serous (parietal and visceral) pericardium and a dilated right atrium almost completely occupied by the tumoral mass. The CT scan revealed invasion of the upper vena cava ostium and anterior mediastinum with pretracheal adenopathies, and hemorrhagic pleural and pericardial effusion suggestive of a sarcoma. The histological examination and immunohistochemistry confirmed the diagnosis of angiosarcoma. Although a rare form of malignant tumor that affects the head, neck, breast, bone, liver, spleen and heart, angiosarcoma must be considered as a possible cause of pleural and pericardial effusion, especially in previously healthy young patients.